Nutritional evaluation, phytochemical makeup, antibacterial and antioxidant properties of wild plants utilized as food by the Gaddis-a tribal tribe in the Western Himalayas - Thakur, Arti; Singh, Somvir; Dulta, Kanika; Singh, Nitesh; Ali, Baber; Hafeez, Aqsa; Vodnar, Dan C.; Marc, Romina Alina (Frontiers in Agronomy, 2022)
Nowadays, it is generally accepted that medicinal plants play a crucial role in traditional healthcare operations, providing hints to new research fields and in biodiversity protection. However, there is a lack of information on the medicinal uses of plants in many of the interior Himalayan regions. In light of this, the current investigation was initiated in the tribally dominant western Himalayan hinterland. The current study examined five underutilized wild edible plants, namely, Allium rubellum, Berberis chitria, Capsella bursa-pastoris, Stellaria aquatica, and Rheum emodi, for their nutritional qualities, phytochemical analysis, antioxidant activity, and antibacterial activity, which are consumed as food by the Gaddi community of the Bharmour region of the Chamba District, Himachal Pradesh. In this study, the nutritional makeup of these plants was examined in terms of their carbohydrate, protein, sodium, potassium, crude fiber, and fat content. As compared to other investigated species, A. rubellum has the highest nutritional content: carbohydrate (6.93 mg/g), protein (10.18 mg/g), sodium (3.21 mg/g), potassium (16.32 mg/g), and fiber (6.46%). In addition, phenols, amino acids, tannins, terpenoids, carotenoids, and phytate were found to be the least significant phytochemicals in R. emodi, i.e., 4.81 mg/g, 0.594 mg/g, 2.204 mg/g, 1.482 mg/g, 156 µg/g, and 0.680%, respectively. The methanolic extract of these wild edible plants showed significant free radical scavenging activity by using ABTS and DPPH assays. Moreover, the antibacterial activity of the methanolic extract of studied plants based on the present study suggested that R. emodi exhibits a maximum zone of inhibition of 20.8 mm against Escherichia coli, whereas S. aquatica showed a maximum inhibition zone of 19.2 mm against S. aureus. The findings of this study validated that these wild edible plants are an alternate source of medicine and are an abundant source of various phytochemicals like protein, carbohydrates, vitamins, and minerals. These compositions offer dietary benefits, food security, health benefits, and therapeutic advantages. Hence, in the current study, it was analyzed that there is an urgent need for documentation, conservation, characterization, and evaluation of these underutilized plants for their therapeutic purpose and nutritional supplements.